Deep-Sea ecosystem model of the Condor seamount - Sousa, Janaína Bon (2013)
Seamounts play an important role in the status of food webs and biodiversity in the open ocean. These habitats are now subject to an intensive exploitation and it is urgent to apply an ecosystem perspective towards the development of sustainable fisheries. Ecosystem models offer scope to understand the interactions between fisheries, exploited species and the ecosystem that supports them, enabling impact assessments of human activities on the marine environment. This study describes the construction and input data of an Ecopath with Ecosim model for the Condor seamount ecosystem, located in the Azorean archipelago (NE Atlantic). The model comprises 23 functional groups, including plankton, invertebrates, fishes, marine mammals and seabirds. The fisheries component consists on the regional fleet, with an emphasis on demersal fisheries. This model can serve as a basis for future Ecosim and Ecospace simulations of the effect of fishing on Condor seamount or on other seamounts around the Azorean islands.